2008
DOI: 10.1021/cg800066g
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of β-Helical Antifreeze Protein Mutants with Ice

Abstract: ABSTRACT:The fold of the -helical antifreeze protein from Tenebrio molitor (TmAFP) proved to be surprisingly tolerant of multiple amino acid substitutions, enabling the construction of a panel of mutants displaying grids of single amino acid types in place of the threonines on the ice-binding face. These mutants, maintaining the regularity of amino acid spacing found in the wildtype protein but with different functional groups on the surface, were tested for antifreeze activity by measuring thermal hysteresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 59 publications
3
46
1
Order By: Relevance
“…The dependence of the FH activity on the time that was allowed for the adsorption of AFPs on an ice crystal was examined for GFP-TmAFP with a custom-built nanoliter osmometer (32). We found that the FH activity increased with the time of exposure of the ice crystals to an AFP solution.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of the FH activity on the time that was allowed for the adsorption of AFPs on an ice crystal was examined for GFP-TmAFP with a custom-built nanoliter osmometer (32). We found that the FH activity increased with the time of exposure of the ice crystals to an AFP solution.…”
Section: Resultsmentioning
confidence: 99%
“…Both systems were validated to give comparable results. The nanoliter osmometer experiments were conducted in a cell that has been described previously in detail (14,42,43). The temperature of the custom-designed nanoliter osmometer was controlled through a LabView interface developed by Ido Braslavsky.…”
Section: Methodsmentioning
confidence: 99%
“…Bar et al arrive at a similar conclusion based on a systematic study of ice-shaping and TH activity of TmAFP mutants. 125 Drori et al studied whether IBPs must be present in solution to block desorption and ice crystal growth. To this end, unbound TmAFP surrounding the ice crystal was removed, by buffer exchange in the TH gap.…”
Section: B Reversible or Irreversible Ice-binding?mentioning
confidence: 99%